Floristic Composition and Natural History Characteristics of Dry Forests in the Pacific - Gillespie, T.; Keppel, Gunnar; Pau, S.; Price, J.; Jaffre, T.; Meyer, J.; O'Neill, K. (University of Hawaii Press, 2011)
We compare the floristic composition of tropical dry forests at the stand level using Gentry's transect method (0.1 ha) in some of the largest and highest-quality remaining fragments in the Pacific (Hawai'i, 15 sites; Fiji, 9; the Marianas, 3; the Marquesas, 6; New Caledonia, 7) and compare results with neotropical dry forests. A total of 299 species or morphospecies =2.5 cm diameter at breast height were identified from all 40 sites in the Pacific. Rubiaceae (28 spp.), Euphorbiaceae (25 spp.), Fabaceae (23 spp.), Sapindaceae (18 spp.), and Myrtaceae (17 spp.) were the most speciose families in Pacific dry forest; however, no family dominated across regions in the Pacific. The most common species by frequency and density in each region were native with the exception of Hawai'i, which contains a high number of nonnative species. Observed and estimated (Chao 2) levels of native species richness show that New Caledonia and Fiji contain the highest species richness followed by Hawai'i, the Marianas, and the Marquesas. There is very little overlap at the native species level among regions, with Hawaiian dry forests the most dissimilar at the native species, genus, and family level and New Caledonia and Fiji the most similar. Unlike mainland neotropical dry forest, dry forests in the Pacific contain very few deciduous species and a low proportion of wind-dispersed species.There is a high proportion of dioecious species in Hawai'i, which is similar to the neotropics; however, other Pacific regions have fewer dioecious species.